Evaluation of the usefulness of direct laryngoscopy and video laryngoscope training in pediatric airway management - Kim, Jin-Hwa; Kim, Hyun-Jung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study aims to evaluate the usefulness of direct laryngoscope and video laryngoscope education in pediatric airway management of 119 paramedics. Methods/Statistical analysis: The study subjects were 37 first-class emergency medical personnel working at two fire stations located in J area. Secure normal airways, fixation of head and cervical vertebrae, performance of endotracheal intubation and confidence in tongue edema were assessed before and after training. Collected data were analyzed using frequency, descriptive statistics, and paired t-test by SPSS 22.0. Findings: Total endotracheal intubation scores in endotracheal intubation performance according to the type of laryngoscope was significantly higher in tongue edema situation with video laryngoscope before training (p=.024) and in head and cervical vertebral fixation situation with direct laryngoscope after training (p=.015). Endotracheal intubation time was faster in three cases of direct laryngoscope before and after training (p =.003, p=.040, p=.040), and faster in normal airway (p=.004) as well as tongue edema (p=.006) significantly. In the tongue edema, the tooth injury rate was decreased by video laryngoscope (p <.001, p = .001) before and after education and the confidence in performing endotracheal intubation was higher in direct laryngoscope (p <.001) and video laryngoscope (p<.001) after training. Improvements/Applications: In addition to direct laryngoscopy, continuous video laryngoscope training through a variety of on-site situations is required for effective childhood airway management of 119 paramedics.